Chirality specific and spatially uniform synthesis of single-walled carbon nanotubes from a sputtered Co–W bimetallic catalyst. Issue 30 (14th July 2016) - An, Hua; Kumamoto, Akihito; Takezaki, Hiroki; Ohyama, Shinnosuke; Qian, Yang; Inoue, Taiki; Ikuhara, Yuichi; Chiashi, Shohei; Xiang, Rong; Maruyama, Shigeo
Abstract : Chirality specific and spatially uniform single-walled carbon nanotubes are synthesized by sputtered Co-W catalyst. An intermediate structure of catalyst is identified. Abstract : Synthesis of single-walled carbon nanotubes (SWNTs) with well-defined atomic arrangements has been widely recognized in the past few decades as the biggest challenge in the SWNT community, and has become a bottleneck for the application of SWNTs in nano-electronics. Here, we report a selective synthesis of (12, 6) SWNTs with an enrichment of 50%–70% by chemical vapor deposition (CVD) using sputtered Co–W as a catalyst. This is achieved under much milder reduction and growth conditions than those in the previous report using transition-metal molecule clusters as catalyst precursors ( Nature, 2014, 510, 522). Meanwhile, in-plane transmission electron microscopy unambiguously identified an intermediate structure of Co6 W6 C, which is strongly associated with selective growth. However, most of the W atoms disappear after a 5 min CVD growth, which implies that anchoring W may be important in this puzzling Co–W system.